Fe-Ni bimetallic supported on mordenite catalyst for selective oxidation of veratryl alcohol in a continuous reactor - N. Gayathri; P. Tamizhdurai; C. Kavitha; V.L. Mangesh; P. Santhana Krishnan; A. Vijayaraj; R. Kumaran; Nadavala Siva Kumar; Ahmed S. Al-Fatesh; Salwa B. Alreshaidan (Arabian Journal of Chemistry, 2024)
Veratryl alcohol (VA) is preferentially oxidized to veratraldehyde (VADE) using a heterogeneous catalyst, which is more favoured in industries. Commercial mordenite (Ca,Na2,K2) Al2Si10O24·7H2O) was desilicated with NaOH and loaded with nickel and iron bimetal by the wet impregnation method. The synthesised Mordenite-Fe(5 %)/Ni(5–20 %) bimetallic catalyst, possessing active Bronsted acid sites, was employed to selectively oxidize the veratryl alcohol reaction. FT-IR, XRD, BET, HR-SEM, HR-TEM, and TPD were employed to determine the catalyst's textural attributes, morphology, chemical properties, and stability. Selective oxidation was performed over the catalysts using TBHP as an oxidant in a continuous reactor. To examine the most active catalyst among the four and to maximise the conversion and yield, the reaction conditions are optimised for various reaction parameters The reaction conditions were optimized by attaining 100 % conversion at temperature (90° C) for time (2 hr) and a maximum conversion of 97 % and a selectivity of 99 % at 10 bar pressure, WHSV (1.0 h−1) with acetonitrile solvent. The result of the study display that Fe (5 %) and Ni(15 %) impregnated on mordenite exhibits excellent catalytic stability with conversion (100 %) and selectivity (99 %) among the other catalysts. During regeneration, the conversion rate declined from 99.5 to 92.4.7 % and selectivity declined from 100 % to 96.2 % at the end of the seventh cycle. The high selectivity and stability of MOR-Fe(5 %)/Ni(15 %) imply that they might function properly as appropriate catalysts for the oxidation of aromatic alcohols. The advantages of the current synthesis are its cost-efficiency and eco-friendliness.